2021
DOI: 10.3390/foods10102285
|View full text |Cite
|
Sign up to set email alerts
|

Sprouting Time Affects Sorghum (Sorghum bicolor [L.] Moench) Functionality and Bread-Baking Performance

Abstract: Despite being considered a climate-resilient crop, sorghum is still underutilized in food processing because of the limited starch and protein functionality. For this reason, the objective of this study was to investigate the effect of sprouting time on sorghum functional properties and the possibility to exploit sprouted sorghum in bread making. In this context, red sorghum was sprouted for 24, 36, 48, 72, and 96 h at 27 °C. Sprouting time did not strongly affect the sorghum composition in terms of total star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
8
0
1
Order By: Relevance
“…The results showed that the firmness of the breads was significantly ( p ≤ 0.05) different as a function of genotype. A negative correlation between volume and crumb firmness (r = −0.76, p < 0.05) was obtained, which is consistent with previous results [ 54 , 55 ]. The einkorn genotypes had the highest values for bread firmness, while Cappelli and Giovanni Paolo were the softest.…”
Section: Resultssupporting
confidence: 92%
“…The results showed that the firmness of the breads was significantly ( p ≤ 0.05) different as a function of genotype. A negative correlation between volume and crumb firmness (r = −0.76, p < 0.05) was obtained, which is consistent with previous results [ 54 , 55 ]. The einkorn genotypes had the highest values for bread firmness, while Cappelli and Giovanni Paolo were the softest.…”
Section: Resultssupporting
confidence: 92%
“…Scientific research in the field of functional ingredients in the bakery industry has led to the production of products with varying degrees of replacement of wheat flour, for example, with partially defatted hemp seeds [ 17 ], Jerusalem artichoke tubers [ 18 ], oats [ 19 ], buckwheat [ 20 ], green tea [ 21 ], Pleurotus Ostreatus fibers (1,3/1,6 Beta-glucan) [ 22 ], various by-products from the fruit and vegetable processing industry, millets [ 23 ], sorghum [ 24 ], amaranth [ 25 , 26 ], quinoa [ 27 ], sunflower seeds [ 28 ], flaxseeds [ 29 ], pumpkin seeds [ 30 ], lupine [ 31 ], chia seeds [ 32 ], peas [ 33 ], chickpeas [ 34 ], lentils [ 35 ], chestnuts [ 36 ], and cricket flour [ 37 ], with important effects in terms of increasing the content of fiber, minerals, protein, vitamins, antioxidants, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the magnificent effect of dextran produced in situ by Weissella confusa A16 on modifying the flavor and texture of sorghum-wheat composite dough was observed. Compared with the original bread, sorghum-wheat composite dough enriched with dextran produced in situ can produce soft, high moisture, and foldable bread [123]. This was observed in a study that used a sorghum-wheat composite dough ratio of 1:1 and enriched it with a dextran rate of 0.56% of the bread weight [124].…”
Section: Dextranmentioning
confidence: 86%
“…Crumb firmness is expressed in N. (Adapted from Ref. [123] with permission of MDPI. copyright 2021).…”
Section: Dextranmentioning
confidence: 99%